2017
DOI: 10.1039/c7nr05402e
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine-based coordination polymer nanoparticles for enhanced photodynamic therapy

Abstract: In the photodynamic therapy (PDT) of cancer, zinc phthalocyanine (ZnPc) as a photosensitizer possesses superior photosensitive properties. However, the therapeutic effect of ZnPc in PDT is limited due to its aggregation, low solubility and poor selectivity. In this study, charge-reversal phthalocyanine-based coordination polymer nanoparticles (PCPN) are developed for improving the curative effect of ZnPc. Tetra(4-carboxyphenoxy)-phthalocyaninatozinc(ii) (TPZnPc) is coordinated with the zinc ion to form the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…[32][33][34] Owing to their unique structures and various functional properties, including excellent semiconductor properties and catalytic activities, MPc derivatives have been widely used in various elds including catalysis, sensors, and photodynamic therapy. [35][36][37][38][39][40][41][42] Due to its redox activity, catalytic activity, and carrier transport ability result from the extended p-system, MPc complexes have been used as the linking units in 2D MOFs, which show good stability, conductivity, redox activity, and electrocatalytic activity. [43][44][45] Here, we developed a novel electrochemical sensor based on an iron phthalocyanine (FePc) MOF for the sensitive detection of vanillin.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Owing to their unique structures and various functional properties, including excellent semiconductor properties and catalytic activities, MPc derivatives have been widely used in various elds including catalysis, sensors, and photodynamic therapy. [35][36][37][38][39][40][41][42] Due to its redox activity, catalytic activity, and carrier transport ability result from the extended p-system, MPc complexes have been used as the linking units in 2D MOFs, which show good stability, conductivity, redox activity, and electrocatalytic activity. [43][44][45] Here, we developed a novel electrochemical sensor based on an iron phthalocyanine (FePc) MOF for the sensitive detection of vanillin.…”
Section: Introductionmentioning
confidence: 99%
“…The authors designed NCPs containing tetra(4-carboxyphenoxy)-phthalocyaninatozinc(II) (TPZnPc) photosensitizer coordinated with zinc ions. The preformed nanoparticles were coated with a lipid bilayer containing 1,2-dicarboxylic-cyclohexane anhydride modified lysyl-cholesterol (DLC) that promotes tumor cellular uptake through an electrostatic interaction induced by the mildly acidic tumor microenvironment [90]. These NCPs were proved to enhance selective tumor cellular uptake and generate more intracellular 1 O 2 after irradiation in vivo, which demonstrates the potential application of these NCPs in effective PDT ( Figure 5).…”
Section: Development Of Targeting Ncps For Photodynamic Therapymentioning
confidence: 97%
“…(a) Preparation of the nanoparticles, and (b) accumulation in the tumor after intravenous administration, which is followed by its charge-reversal ability to improve the selective uptake and effective PDT in tumor cells after laser irradiation. The figure is reproduced from Reference[90] with the permission from American Chemical Society.…”
mentioning
confidence: 99%
“…4,11−12 Among the reported MCPs, porphyrin-based MCPs are widely studied. [13][14][15][16] Porphyrins are well-known photosensitizers for photodynamic therapy due to their highly e cient singlet oxygen 1 O 2 generation under light irradiation. [16][17] Moreover, Zheng et, al reported that porphyrins could possess photothermal conversion capability when porphyrins aggregated with high packing density.…”
Section: Introductionmentioning
confidence: 99%